(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Coeliac disease is an autoimmune disorder that occurs in genetically predisposed people of all ages from middle infancy to onwards. It is a disease in which the mucosal lining of the small intestine is damaged in response to ingestion of gluten and similar proteins, which are found in wheat, oats, rye, barley and other grains. Symptoms include chronic diarrhoea, failure to thrive and fatigue; however these may be absent and symptoms in other organ systems have been reported. In this case report, a 6 year-old girl presented with recurrent diarrhoea with growth failure and itchy skin rashes. Physical examination showed that the patient was moderately pale and had generalized oedema with discrete erythematous, papular lesions over different parts of the body. Serum for tissue transglutaminase (IgA) antibody was raised. Duodenal biopsy was obtained and histopathological diagnosis was compatible with coeliac disease. The patient was treated with supportive management and was advised for life long gluten free diet. The patient improved within short period after withdrawal of gluten from diet. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16254 J Shaheed Suhrawardy Med Coll, 2013;5(1):55-58